Risiko Outsourcing Vendor Teknologi: Vendor Lock-In Lms Cloud Perguruan Tinggi - Ginanjar Nugraha; Rika Setiani Nur Faidah; Rike Setiani Nur Fadillah; Umi Lutfiatul Fadilah; Nur Kesha Sophiawati; Devi Perdiansyah; Derismana Derismana (Apik Cahaya Ilmu, 2026)
Information technology outsourcing, particularly through the adoption of cloud-based services, has been widely implemented by higher education institutions to improve efficiency and flexibility in academic services. Despite its potential benefits, outsourcing practices also introduce several strategic risks, one of the most significant being vendor lock-in. Vendor lock-in occurs when an institution becomes highly dependent on a single technology provider, resulting in high costs, time, and risks associated with switching to alternative vendors. This article aims to identify the risks of information technology outsourcing and technology vendors in higher education institutions, with a specific focus on vendor lock-in risks in the implementation of cloud-based Learning Management Systems (LMS). The study employs a targeted literature review of twelve international journal articles related to IT outsourcing, cloud computing, and risk management. The findings indicate that vendor lock-in is a dominant risk closely associated with contract and Service Level Agreement (SLA) issues, data security and privacy concerns, hidden costs, and the loss of internal control and competencies. These risks have significant economic impacts through increased switching costs and budget uncertainty, as well as educational impacts through potential disruptions to learning services and risks to academic data security. This article recommends strong contract design, early exit strategies, the adoption of open standards, and the strengthening of internal competencies as key measures to mitigate vendor lock-in risks in higher education institutions. Keywords: IT outsourcing; vendor lock-in; cloud computing; learning management system; risk management